Kompetensi Sosial Guru Pendidikan Agama Kristen Dan Motivasi Belajar Siswa - Sumual, Ferry J N; Palempung, Franty Faldy (Jurnal Lentera Nusantara, 2021)
This paper specifically outlines the social complexion of Christian religious educators to increase the learning interest of learners. This paper uses qualitative methods with a survey approach accompanied by literature. Social competition is something that needs to be developed by a teacher so that he can build students' learning interests. As for social competence, among others, Skilled to Communicate, sympathetic, Have the ability to work with anyone, as well as have the ability to get along and partner with fellow educators. With the social complement that an educator has, the potential to build and improve the learning of learners will be created. Although it can not instantly build student learning motivation, but with the competence of educators it is the foundation in the future. Indeed, there are many factors that can move the motivation of learners to learn, But it all must start from the educator as a role model for all students who are taught.AbstrakTulisan ini secara spesifik menguraikan komptensi sosial pendidik agama Kristen untuk meningkatkan minat belajar peserta didik. Tulisan ini menggunakan metode kualitatif dengan pendekatan survei disertai literatur. Komptensi sosial merupakan hal yang perlu dikembangkan oleh seorang guru agar ia dapat membangun minat belajar siswa. Adapun kompetensi sosial itu diantaranya, terampil berkomunikasi, simpatik, Memiliki kemampuan bekerjasama dengan siapa saja, serta  memiliki kemampuan bergaul dan bermitra pada rekan sesama pendidik.  Dengan komptensi sosial yang dipunyai seorang pendidik, potensi membangun dan meningkatkan belajar nara-didik akan tercipta. Walau tidak bisa secara instan membangun motivasi belajar siswa, namun dengan kompetensi dari pendidik itu merupakan fondasi dikemudian hari. Memang ada banyak faktor yang dapat menggerakkan agar motivasi peserta didik untuk belajar, namun itu semua harus diawali dari tenaga pendidiknya sebagai role model bagi seluruh siswa yang diajar.